2019
DOI: 10.1186/s13052-019-0676-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative two time-point proteome analysis of the plasma from preterm infants with and without bronchopulmonary dysplasia

Abstract: Background In this study, we aimed to analyze differences in plasma protein abundances between infants with and without bronchopulmonary dysplasia (BPD), to add new insights into a better understanding of the pathogenesis of this disease. Methods Cord and peripheral blood of neonates (≤ 30 weeks gestational age) was drawn at birth and at the 36th postmenstrual week (36 PMA), respectively. Blood samples were retrospectively subdivided into BPD(+) and BPD(−) groups, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Analysis of bronchoalveolar lavage fluid in preterm babies using a proteomics-based approach showed that calcium signaling-related proteins differed with BPD severity 37 . In a study evaluating plasma proteins using proteomics in preterm infants, it was noted that there was decreased gelsolin, afamin, and carboxypeptidase N subunit 2 levels in cord blood 38 . In addition, there was decreased hemoglobin subunit gamma-1 and galectin-3 binding protein levels, along with increased serotransferrin in plasma at 36 weeks PMA 38 .…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of bronchoalveolar lavage fluid in preterm babies using a proteomics-based approach showed that calcium signaling-related proteins differed with BPD severity 37 . In a study evaluating plasma proteins using proteomics in preterm infants, it was noted that there was decreased gelsolin, afamin, and carboxypeptidase N subunit 2 levels in cord blood 38 . In addition, there was decreased hemoglobin subunit gamma-1 and galectin-3 binding protein levels, along with increased serotransferrin in plasma at 36 weeks PMA 38 .…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…In a study evaluating plasma proteins using proteomics in preterm infants, it was noted that there was decreased gelsolin, afamin, and carboxypeptidase N subunit 2 levels in cord blood 38 . In addition, there was decreased hemoglobin subunit gamma-1 and galectin-3 binding protein levels, along with increased serotransferrin in plasma at 36 weeks PMA 38 . In a recent study by Förster et al ., proteomic screening was utilized in plasma samples from preterm infants to identify novel biomarkers of BPD that could help in the early identification of such infants.…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…The participant gestational age at birth ranged from < 23 to 37 weeks, with sample sizes varying from 4 to 77 participants. Most studies used a tandem Mass Spectrometry method (MS/MS) to analyse the proteins of interest [ 10 , 12 15 ]. Three of the fourteen studies also conducted protein validation and completed this task using protein microarray and immunoassay techniques [ 10 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…24 However, these metabolites need to be measured in special labs and are therefore less useful as clinical diagnostic tests. Also, laborious plasma proteome analyses 25 showed changes in the concentrations related to infections in BPD. Furthermore, neutrophil-to-lymphocyte ratio in blood 26 is an early predictor of BPD.…”
Section: Re Sultsmentioning
confidence: 99%